2022
DOI: 10.1111/jpn.13779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginger (Zingiber officinale) supplementation on testicular histology, semen characteristic, blood plasma parameters and reproductive performance in aged broiler breeder roosters

Abstract: Higher long-chain polyunsaturated fatty acids contents in roosters' sperm plasma membrane along with age-related decrease in antioxidant defense make the spermatozoa very susceptible to lipid peroxidation. Ginger root contains abundant amounts of gingerol, shogaols, gingerdiol and other active compounds, which known as antioxidant compounds to enhance semen quality. The goal of the study was to evaluate the effect of dietary supplementation of ginger root on semen quality, blood chemistry, immune response, tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Authaida et al (2024) , found that Thai ginger (Kaempferia parviflora) extract improved sperm production, semen preservation, and fertility in Thai native chickens under heat stress conditions. Similarly, Nemati et al (2023) , demonstrated that ginger (Zingiber officinale) supplementation enhanced testicular histology, semen characteristics, blood plasma parameters, and reproductive performance in aged broiler breeder roosters. Their study showed that the antioxidant compounds like gingerol, shogaols and gingerdiol in ginger root helped enhance semen quality by reducing lipid peroxidation in the sperm plasma membrane of aged roosters.…”
Section: Discussionmentioning
confidence: 98%
“…Authaida et al (2024) , found that Thai ginger (Kaempferia parviflora) extract improved sperm production, semen preservation, and fertility in Thai native chickens under heat stress conditions. Similarly, Nemati et al (2023) , demonstrated that ginger (Zingiber officinale) supplementation enhanced testicular histology, semen characteristics, blood plasma parameters, and reproductive performance in aged broiler breeder roosters. Their study showed that the antioxidant compounds like gingerol, shogaols and gingerdiol in ginger root helped enhance semen quality by reducing lipid peroxidation in the sperm plasma membrane of aged roosters.…”
Section: Discussionmentioning
confidence: 98%
“…Samples were held on ice and within 2 h of collection they were centrifuged at 1300 × g for 15 min to separate the serum from the plasma, the former frozen at −20 °C until analysis. Serum concentrations of urea (using enzymatic Urease-GLDH method; mg/dL), triglycerides (Catalogue number: 117,500; mg/dL), total cholesterol (Catalogue number: 128,500; mg/dL), low density lipoprotein cholesterol (using enzymatic methods; mg/dL), high density lipoprotein cholesterol (mg/dL), aspartate amino transferase (Catalogue number: 118,400; U/L), alanine amino transferase (U/L), alkaline phosphatase (Biochrom WPA Biowave S2100 Diode Array Spectrophotometer; U/L), and lactate dehydrogenase were quantified as per the manufacturer's instructions of the listed laboratory kits (Pars Azmoon Co., IRN) and a benchtop autoanalyzer (ALCYON-300, Abbott, USA) ( Nemati et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%